Towards Efficient Abstractions for Concurrent Consensus - KOUTAVAS, VASILEIOS (Springer Berlin Heidelberg, 2013)
Consensus is an often occurring problem in concurrent and distributed programming. We present a programming language with simple semantics and build-in support for consensus in the form of communicating transactions. We motivate the need for such a construct with a characteristic example of generalized consensus which can be naturally encoded in our language. We then focus on the challenges in achieving an implementation that can efficiently run such programs. We setup an architecture to evaluate different implementation alternatives and use it to experimentally evaluate runtime heuristics. This is the basis for a research project on realistic programming language support for consensus
Lecture Notes in Computer Science
Trends in Functional Programming
PUBLISHED
Provo, Utah, USA
Keywords: Concurrency; Programming Languages